Pengembangan Rencana Pembelajaran Semester (RPS) Mata Kuliah Mahārat al-Istimā‘ Berbasis Kecakapan Abad 21 - Sukirman; Zaenuri, Muhammad; Hasanah, Luthfi Qoriatul (Universitas Negeri Jakarta, 2023)
Education is currently faced with the 21st century, where students need various skills in addition to knowledge content. This study aims to develop semester lesson plan (Rencana Pembelajaran Semester/RPS) in the mahārat al-istimā‘ course, Arabic Language Education study program at UIN Raden Mas Said Surakrta. The method used in this research is research and development (R & D). The R & D procedure used in this research is the development model of Successive Approximation Models 1 (SAM 1) which was introduced by Micheal W. Allen. The results show that based on needs analysis, some shortcomings were found in the RPS of mahārat al-istimā‘. Subject learning outcomes (CPMK) in each RPS field have not been integrated. The difference in CPMK in courses in the same plot is enough to show that the design of the mahārat al-istimā‘ course is not related. The RPS design developed is to make a rough RPS design using the KKNI and MBKM models. The results of product evaluation on experts are quite good. This means that the mahārat al-istimā‘ RPS that is developed is integrated with each other.